Inside Cover: Allosteric Indicator Displacement Enzyme Assay for a Cyanogenic Glycoside (Chem. Eur. J. 43/2013). Issue 43 (14th October 2013) - Jose, D. Amilan; Elstner, Martin; Schiller, Alexander
<x xml:space="preserve">Abstract</x> Toxic cyanogenic glycosides can be found in bitter almonds and apricots pits. A chemical biosensor for the selective detection of amygdalin in aqueous solution is reported by A. Schiller et al. in their Full Paper on page 14451 ff. The hybrid sensor consists of the enzyme β‐glucosidase and a boronic acid appended viologen together with a fluorescent reporter dye. β‐Glucosidase degrades the amygdalin into hydrogen cyanide, glucose and benzaldehyde. Only the released cyanide binds at the allosteric site of the boronic acid.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>